Penganut Agama Kepercayaan Dan Problem Kebebasan Berkeyakinan Di Indonesia: Perspektif Sosiologi Agama - Abd Hannan (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
The issue of religious belief is a religious issue that has been inviting a lot of debate, both theoretical and practical. Although their existence has been legitimized through a decision by a state institution, the Constitutional Court (MK), in fact, still invites quite a heated debate among the public. This study examines the social rights of religious freedom of believers. There are three research questions to be answered in this study; What are the concepts of trust and social rights? How are the dynamics of believers in the context of religious freedom in Indonesia? What is the reality of the social rights of believers, from the perspective of the sociology of religion? The three questions are aimed at knowing the concepts of trust and social rights; describing the reality of believers in Indonesia; conduct an in-depth study of the social rights of believers, viewed from the perspective of the sociology of religion. This study is a field study that uses qualitative research. There are two data used, primary data and secondary data. In general, the findings of this study contain an in-depth explanation of the concept of belief and social rights, a narrative description of the existence of believers in Indonesia, as well as a sociological explanation of the meaning of social rights, in relation to believers in Indonesia. In general, this paper makes a major contribution in terms of providing a sociological explanation of the existence and dynamics of Indonesian believers in the future. Keywords: Religious Freedom, Religious Belief, Sociology of Religion. Isu penghayat kepercayaan merupakan isu keagamaan yang hingga sekarang mengundang banyak perdebatan, baik itu perdebatan pada wilayah teoritis maupun praktis. Meski keberadaan mereka telah mendapat legitimasi melalui putusan lembaga negara, Mahkamah Konstitusi (MK), namun pada faktanya tetap mengundang perdebatan cukup hangat di kalangan publik. Studi ini mengkaji hak sosial kebebasan beragama kaum penghayat kepercayaan. Terdapat tiga pertanyaan penelitian yang akan dijawab dalam studi ini; Apa yang dimaksud dengan konsep kepercayaan dan hak sosial kebebasan beragama? Bagaimana dinamika penganut kepercayaan dalam konteks kebebasan beragama di Indonesia? Bagaimana realitas hak sosial kebebasan beragama penganut kepercayaan, ditinjau dari perspektif sosiologi agama? Tiga pertanyaan tersebut ditujukan untuk mengetahui konsep kepercayaan dan hak sosial; mendeskripsikan realitas penganut kepercayaan di Indonesia; melakukan kajian mendalam perihal hak sosial penghayat kepercayaan, ditinjau dari perspektif sosiologi agama. Studi ini merupakan kajian lapangan yang menggunakan jenis penelitian kualitatif. Data yang digunakan ada dua, data primer dan data sekunder. Secara umum, temuan studi ini berisikan penjelasan mendalam tentang konsep kepercayaan dan hak sosial, deskripsi naratif eksistensi penganut kepercayaan di Indonesia, serta penjelasan sosiologis perihal makna hak sosial, kaitannya dengan penganut kepercayaan di Indonesia. Secara umum, tulisan ini memberi sumbangsih besar dalam hal memberi penjelasan sosiologis eksistensi dan dinamika penganut kepercayaan Indonesia ke depan. Kata Kunci : Kebebasan Beragama, Agama Kepercayaan, Sosiologi Agama